The therapeutic effects of natural organosulfur compounds on atherosclerosis and their potential mechanisms: a comprehensive review - Tang, Yuanyuan; Lv, De; Tao, Yijing; Wang, Juan (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis (AS) is a major cause of cardiovascular disease morbidity and mortality, characterized by lipid accumulation, oxidative stress, and chronic inflammation. Natural organic sulfur compounds (OSCs), especially those derived from garlic (Allium sativum), have therapeutic value in slowing the course of AS. We systematically evaluate the mechanisms by which OSCs exert their anti-atherogenic effects, focusing on lipid metabolism regulation, antioxidant defense, anti-inflammatory responses, endothelial protection, and antibacterial activity. Key signaling pathways, including Nrf2/ARE, RhoA/ROCK, AMPK/SREBP-1c/SREBP-2, and PCSK9-LDLR, are highlighted as critical mediators of these effects. Preclinical and clinical investigations show that OSCs significantly reduce plasma cholesterol, suppress oxidative stress, and attenuate inflammatory cascades. However, challenges such as variable bioavailability and the absence of standardized formulations limit their clinical application. Future research should focus on clinical trials to establish efficacy, improve bioavailability, and create standardized formulations of OSCs for cardiovascular disease prevention and management.